UTILIZATION OF MULTIBEAM ECHOSOUNDER DATA FOR BATHYMETRY MAPPING: EVALUATION WITH INTERNATIONAL STANDARD - Nadzir, Zulfikar Adlan; Munthe, Manson Brian Utama (Engineering Faculty Universitas Lampung, 2025)
Bathymetric mapping is crucial for understanding seabed conditions, especially in maritime countries like Indonesia. This study evaluates the quality of bathymetric data acquired using Multibeam Echosounder (MBES) in Jakarta waters. The acquired data was processed and analyzed based on the international standard IHO S-44. The results show that most acquired bathymetric data met the specified accuracy standard. However, some data did not meet the standard, especially in areas with varying depths. Bathymetric maps and seabed slope classification maps were successfully produced. The bathymetric map shows the complex morphology of the seabed, while the slope classification map indicates the dominance of flat areas. This research contributes significantly to efforts to improve the quality of bathymetric data in Indonesia.